2020
DOI: 10.6024/jmbai.2020.62.1.2098-04
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen new records of Batoids (Elasmobranchii) from waters off Andaman and Nicobar Islands, India

Abstract: Marine waters of Andaman and Nicobar Islands, India in the tropical Indian Ocean, is a poorly explored high faunal diverse region. The present study documents new records of batoids from the region, identified during the fishery and diversity monitoring surveys conducted during November 2016 to June 2019 at different fish landing centers of Andaman and Nicobar Islands. Fifteen elasmobranch species including 2 wedgefishes, 1 skate and 12 rays were identified and confirmed as new reports for the region. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Caesio striata is known to be confined to the Gulf of Aden and the Red Sea (Fricke et al, 2023; Holleman et al, 2013), and its occurrence in the Laccadive archipelago needs to be confirmed using voucher specimens and supporting genetic data. Pisinnicaesio pisang , a widely distributed species in the Indo‐West Pacific ranging from South Africa to Australia (Fricke et al, 2023), has been recorded previously from the Laccadive group of islands (Jones & Kumaran, 1964), where it represented a very minor part of the live bait fishery, mostly concentrated in the Minicoy Islands (Nasser, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Caesio striata is known to be confined to the Gulf of Aden and the Red Sea (Fricke et al, 2023; Holleman et al, 2013), and its occurrence in the Laccadive archipelago needs to be confirmed using voucher specimens and supporting genetic data. Pisinnicaesio pisang , a widely distributed species in the Indo‐West Pacific ranging from South Africa to Australia (Fricke et al, 2023), has been recorded previously from the Laccadive group of islands (Jones & Kumaran, 1964), where it represented a very minor part of the live bait fishery, mostly concentrated in the Minicoy Islands (Nasser, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Hemigaleus microstoma (Sicklefin weasel shark) generally lives in shallow waters and is distributed along the waters of India, China, and Southeast Asia. It has a relatively small body size and spends much time on the bottom of the water by preying on biota that belong to the cephalopod class (Bineesh et al, 2020). Sphyrna lewini (Scalloped hammerhead) has a long front dorsal fin body morphology, a shorter hind dorsal fin, and a long caudal fin tip.…”
Section: Kondship and Populatıon Statusmentioning
confidence: 99%